Generation Z’s Investment Determinants In Sharia Mutual Fund - Sunarsih, Uun; Pradilla, Sabhita Aufa; Rusmanto, Toto; Suryani; Hendryadi (IQTISHODUNA: Jurnal Ekonomi Islam, 2023)
The Sharia financial industry has developed rapidly, including Sharia banks, capital markets, and other financial products, thus providing more choices to investors who want to invest per Sharia principles. This study investigated the impact of minimum capital, Islamic financial literacy, investment risk, returns, and social media on the investment decisions of Generation Z in Islamic mutual funds. The data was collected from a questionnaire distributed in Jakarta, which yielded 390 valid responses. Regression analysis revealed that minimum capital, financial literacy, investment risk, returns, and social media significantly influence investment decisions in Islamic mutual funds. The study found that social media and investment risk were the two most significant factors affecting investment decisions, followed by minimum capital, returns, and financial literacy. The minimum capital of investors' decision-making in Sharia mutual fund investment has yet to be thoroughly explored in the literature, especially in the Indonesian context. Moreover, this study contributes to the behavior of Gen Z investors in the Islamic investment research area.